Measuring course learning outcome in FCSIT - Foo,, Chun Hwa (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Course learning Outcomes (CLO) plays an important role in identifying and evaluating the learning achievements of students in a particular course. CLO is also important to support the course assessment measurement and evaluation. Currently, effective method to measure how successful and achievable the course learning outcome is still lacking. Therefore, this project proposes a system to measure course learning outcome. The proposed system provides the opportunity to study the constructive alignment between course learning outcome and assessment components. The objective of the proposed system is to provide a quantitative measurement system for course instructors to identify and measure the level achievements of the course learning outcome of a particular course in FCSIT. The proposed system allow course instructors to identify the course learning outcome, assessment tools, and assign the percentage of course learning outcome for each assessment. One assessment can consist of few course learning outcomes. A set of calculation formula is designed for the proposed system in measuring the achievement of course learning outcome. The proposed system will generate a report to show the level achievement of course learning outcome for a particular course. The measurement is needed as a basis for course improvement, which also important for continuous quality improvement in overall. learning. An effective measurement system provides a better insight and understanding of the student's competency level achieved in all course learning outcome. Thus, this system will provide value added in continuous learning institution.